Correction: Effect of aspect ratios of rutile TiO2 nanorods on overall photocatalytic water splitting performance. Issue 9 (25th February 2020) - Fu, Bing; Wu, Zhijiao; Cao, Shuang; Guo, Kai; Piao, Lingyu
Abstract : Correction for 'Effect of aspect ratios of rutile TiO2 nanorods on overall photocatalytic water splitting performance' by Bing Fu et al., Nanoscale, 2020, DOI: ; 10.1039/c9nr10870j .